16 Perioperative care of LVAD. (9th April 2018) - Kerk, Ka Lee
Abstract : Introduction: Continuous-flow left ventricular assist devices (LVAD) have emerged as the standard of care for advanced heart failure patients requiring long-term mechanical circulatory support or as bridge to transplant. Evidence-based clinical management of LVAD is becoming increasingly important for optimising outcomes. Preoperative management: Pre-implant optimisation of comorbid conditions is vital in minimising the incidence and severity of post-operative adverse events and for enhancing survival. 1 This includes psychosocial and behavioural screening prior to surgery. Pre-operative education will prepare patient to be self-reliant after device implant. 2 Intraoperative management: Transoesophageal echocardiography (TEE) is essential for identifying valvular pathology and intracardiac defect which may require correction during LVAD implant. 1, 3 Inotropic support should be tailored to the TEE and pulmonary artery catheter findings. A combination of inotropes, inodilators, vasoconstrictors and nitric oxide may be needed and used with care to protect and preserve right ventricular function. Postoperative management: The principles of long-term care include assessment and management of VAD function, haemodynamics, anticoagulation, arrhythmias, infections, and psychosocial factors. 1, 4 Echocardiography is critical in determining optimal pump position and speed setting, and in diagnosing problems with the patient-pump interface. 5 Immobilising the percutaneous lead and exit site care to prevent exit site trauma reduces infection risk. 1 Cardiac rehabilitation is an important component in returning patients to the community. Summary: The success of LVAD support depends on not only surgical implant technique but also judicious pre-operative evaluation/preparation and vigilant management of both immediate and long term post-operative issues. This can be accomplished through the comprehensive care from a multidisciplinary team. References: . Slaughter, et al. Clinical management of continuous-flow left ventricular assist devices in advanced heart failure. J Heart Lung Transplant2010;29:4S:S1–S39. . Martonik H. Caring for patients with a left ventricular assist device. American Nurse Today 2017;12:5. . Sanjay OP. Perioperative management of left ventricular assist devices. Ann Card Anaesth2016;19:S1:19–20. . Feldman, et al. The 2013 international society for heart and lung transplantation guidelines for mechanical circulatory support: Executive summary. J Heart Lung Transplant2013;32:157–187. . Stainback, et al. Echocardiography in the management of patients with left ventricular assist devices: Recommendations from the American society of echocardiography. J Am Soc Echocardiogr2015;28:853–909.